2015
DOI: 10.1111/jace.13942
|View full text |Cite
|
Sign up to set email alerts
|

Large and Stable Shape Memory Effect Realized by Defect Dipoles in Acceptor‐Doped Ferroelectric Ceramics

Abstract: A large and stable shape memory effect has been observed in 0.6 wt% Mn‐doped (Pb0.99Nb0.02)[(Zr0.70Sn0.30)0.52Ti0.48]0.98O3 (Mn:PNZST) ceramics after being poled at high temperature. A maximum shape memory of 0.41% was achieved. This effect is related to the preferentially oriented defect dipoles along the poling direction after poling at high temperature and electric field. Furthermore, the shape memory effect is stable after 104 electric cycles at 30 kV/cm. The shape memory piezoelectric actuator may be fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5] For acceptor doping, oxygen vacancies are created due to the requirement of charge balance and can form defect dipoles with acceptor ions. have an important influence on their properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] For acceptor doping, oxygen vacancies are created due to the requirement of charge balance and can form defect dipoles with acceptor ions. have an important influence on their properties.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of Pb(Ti, Zr)O 3 -based ceramics, the substitutions of Pb 2+ or (Ti, Zr) 4+ by low valent ions of K, Mn, or Fe ions (i.e., acceptor doping) harden the ceramics, giving high mechanical quality factor Q m , low loss tangent tand, and slanted polarization hysteresis loop and high coercive field. [1][2][3][4][5] For acceptor doping, oxygen vacancies are created due to the requirement of charge balance and can form defect dipoles with acceptor ions. These defects play a significant role in stabilizing domain patterns and inducing hardening behavior of the ceramics for various applications in high-power and high-voltage fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this process is quite complicated and the achieved strain memory exhibits serious fatigue problems, which undoubtedly limits its application. 4 Analogous to the imprint electric field, the introduction of internal bias field (E bias ) during poling and aging process in hard type PZT materials, 5,6 2,7 E bias observed in hard type PZT materials is supposed to be related with preferentially oriented defect dipoles along the poling direction. 2,7 On the other hand, from the viewpoint of loading method of applied electric field, sesquipolar loading, referring to the situation where the external field is cycled between a positive electric field E + and a smaller negative electric field E À , is an effective way to increase strain output of piezomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…4 Analogous to the imprint electric field, the introduction of internal bias field (E bias ) during poling and aging process in hard type PZT materials, 5,6 2,7 E bias observed in hard type PZT materials is supposed to be related with preferentially oriented defect dipoles along the poling direction. 2,7 On the other hand, from the viewpoint of loading method of applied electric field, sesquipolar loading, referring to the situation where the external field is cycled between a positive electric field E + and a smaller negative electric field E À , is an effective way to increase strain output of piezomaterials. [8][9][10] For example, it was reported that effective strain of 0.33% was obtained when sesquipolar singal was applied to soft type PZT ceramics, which was two times higher than the unipolar strain.…”
Section: Introductionmentioning
confidence: 99%